METODE BERCERITA SEBAGAI MODEL PENANAMAN PENDIDIKAN AGAMA ISLAM UNTUK ANAK USIA PRASEKOLAH PADA AREA AGAMA TAMAN KANAK- KANAK DI DESA BOGARES KIDUL KECAMATAN PANGKAH KABUPATEN TEGAL - Rizqillah, Ayu Helmy (Indonesian Journal of Early Childhood Education Studies, 2013)
Religion education is important to be given to preschool children to recognize their own religion, the education is a mobilizator and a filter from any aspects of life. This research aims to know the process of story telling as the model of building up Islamic education for preschool children in the kindergarten in Bogares Kidul village. The method used is qualitative descriptive with observational technique, interview, questionnaire, and documentation. The result of the study shows that the story telling method is very effective as the aim to build up Islamic education towards children.Â